Cross comparison of five popular groundwater pollution vulnerability index approaches - Brindha, Karthikeyan; Elango, L. (Elsevier, 2015)
Identification of a suitable overlay and index method to map vulnerable zones for pollution in weathered rock aquifers was carried out in this study. DRASTIC and four models derived from it, namely Pesticide DRASTIC, modified DRASTIC, modified Pesticide DRASTIC and Susceptibility Index (SI) were compared by applying them to a weathered rock aquifer in southern India. The results were validated with the measured geochemical data. This study also introduces the use of temporal variation in the groundwater level and nitrate concentration in groundwater as input and for validation respectively to obtain more reliable and meaningful results. Sensitivity analysis of the vulnerability index maps highlight the importance of one parameter over another for a given hydrogeological setting, which will help to plan the field investigations based on the most or the least influential parameter. It is recommended to use modified Pesticide DRASTIC for weathered rock regions with irrigation practises and shallow aquifers (<20 m bgl). The crucial input due to land use should not be neglected and to be considered in any hydrogeological setting. It is better to estimate the specific vulnerability wherever possible rather than the intrinsic vulnerability as overlay and index methods are more suited for this purpose. It is also necessary to consider the maximum and minimum values of input parameters measured during a normal year in the models used for decision making.